Le Parc National D’al Hoceima: Panorama Entre Terre Et Mer - Hadri, Sarra El; Jaoui, Anouar; Bouziane, Hassan (European Scientific Journal, ESJ, 2019)
Conserving, protecting and enhancing are the main pillars of the creation of National Parks in Morocco. Citing the Al Hoceima National Park characterizing by exclusivities among them one quotes; the presence of emblematic species such as the osprey and cedar, which are the logo symbol of this park, the only one in Morocco that includes a land part and the other marine part and has a view of the Mediterranean Sea, which summarizes a pleasant panorama between land and sea, with a mountainous aspect composed of cliffs and caves that constitute a habitat for monk seals that has disappeared and some bird species such as the osprey, islets and rocks housing several reptile species. This park is a place that meets the needs of land and marine enthusiasts practicing their leisure activities and is also a destination for researchers who participate in the management and preservation of the biodiversity of this environment, which requires the existence of certain cottages by ensuring the comfort and relaxation of visitors in this natural environment in order to develop sustainable tourism with good practice in nature conservation. From this article we focus on the avifauna which is the osprey, also on the plant species concerning the Berber cedar in terms of monitoring and conservation without forgetting the ecotourism which plays a main role in the sustainable development of Al Hoceima National Park by involving the principle of close participation. Conserver, protéger et valoriser sont des piliers principaux de la création des Parcs Nationaux au Maroc. Citant le Parc National d’Al Hoceima caractérisant par des exclusivités parmi eux on cite ; la présence des espèces emblématiques tel que le balbuzard pêcheur et le thuya qui sont le symbole de logo de ce parc ; le seul au Maroc qui englobe une partie terrestre et l’autre partie marine et qui a une vue sur la mer méditerranée ce qui résume un panorama agréable entre terre et mer, avec un aspect montagneux composé des falaises et des grottes, qui constitue un habitat de phoque moine qui a disparu et certains espèces ornithologues comme le balbuzard pêcheur, des îlots et des rochers abritant plusieurs espèces des reptiles. Ce Parc est un endroit qui réponds aux besoins des amateurs pratiquant leurs loisirs et aussi c’est une destination pour les chercheurs qui participent à la gestion et à la préservation de la biodiversité de ce milieu ce qui impose l’existence des certains gites en assurant le confort et la détente des visiteurs dans ce milieu naturel afin de développer le tourisme durable avec la bonne pratique de la conservation de la nature.A partir de cet article on met l’accent sur l’avifaune qui est le balbuzard pêcheur, aussi sur l’espèce végétal concernant le thuya de Berbérie en matière de suivi et conservation sans oublié l’écotourisme qui joue un rôle principale dans le développement durable du Parc National D’al Hoceima en impliquant le principe de la proche participative.